Dentofacial and skeletal pattern in African descendants from southeastern Brazil: clinical prospective study - OLIVEIRA,Teresa Cristina Pereira de (2021)
ABSTRACT Objective: The aim of this study was to evaluate characteristics of African-Brazilians young adults with excellent dental occlusion, including bimaxillary protrusion; compare them to European-American Caucasian standards, and determine whether there is sexual dimorphism in the display of this phenotype. Methods: Lateral cephalometric radiographs were obtained from 43 African-Brazilians within military personnel (28 males and 15 females, average age 22.4 ± 3.4 years) with normal occlusion, selected from a group of 394 volunteers. Thirty-one angular and linear measurements were evaluated. Student’s t-test for independent samples was used to compare results with those established by European-American standards, previously described in the literature. Results: Considering the dentoalveolar pattern, seven angular and six linear measurements showed statistically significant differences (p< 0.001) when compared to Caucasian cephalometric standards. African-Brazilians’ subjects showed lower cranial base angle (SNAr = 119.87 ± 5.66º) and anterior cranial base length (SN-distance = 68.63 ± 4.50 mm) (p< 0.001). The maxilla (SNA = 88.51 ± 3.23º) and the mandible (SNB = 85.06 ± 3.24º) were protruded in relation to the SN line (p< 0.001). Sexual dimorphism was significant for L1.NB (degrees) (p< 0.01), and interincisal angle (U1.L1) (p< 0.05). Conclusion: African-Brazilian young adults presented differences regarding dental and craniofacial characteristics, when compared to European-American norms. It can be stated that Caucasian cephalometric norms should not be applied to African-Brazilian faces.